Imaging of cervical spine traumas. Issue 117 (August 2019) - Izzo, Roberto; Popolizio, Teresa; Balzano, Rosario Francesco; Pennelli, Anna Maria; Simeone, Anna; Muto, Mario
Highlights: This article on investigates the pathophysiological biomechanics involved in the pathogenesis of cervical spine traumas. Classifications for the assessment and management of cervical spine trauma are discussed. The role of Imaging in the evaluation of cervical spine trauma is discussed. Abstract: Spinal traumas represent a significant proportion of muscle-skeletal injuries worldwide. Spinal injuries involve a complex structure with components having different traumatic susceptibility and variable healing capabilities. The interaction of numerous variables at time of trauma creates a great variety of lesions which makes challenging the creation and comparison of homogeneous groups, with difficulties in classifying spinal lesions, in assessing their instability, and in defining the indication and outcome of different treatment strategies. The evolution of concepts on instability has accompanied that of traumas classification schemes and treatment strategies. The assessment of instability in a spinal injury is actually crucial in front of newer surgical techniques and hardwares. Despite a long history of attempts to classify spinal traumas, it remains some degree of controversy in describing imaging data and a wide variety of treatment strategies. Acute cervical spine injuries affect from 1.9% to 4.6% of subjects reporting a blunt trauma, and up to 5.9% of multiple-injured patients. Most of spinal cord injuries are a consequence of unstable fractures of the cervical spine. An accurate and early diagnosis is mandatory to prevent neurological damage in unstable fractures. Classic and newer classifications are primarily based on features identifiable by using conventional imaging and CT scan, which are the most available modalities at most trauma centers. Even though multidetector-CT remains superior in assessing with high accuracy bone injuries, MRI is the most sensitive modality for detecting soft tissues injuries and spinal cord damage.